The Effect of Human Resources Capabilities, Application of Systems of Internal Control, and The Use of Information Technology on The Quality of Local Government Accountability Report - Firda Idzdiana; Ratno Agriyanto; Firdha Rahmiyanti (Faculty of Economics, Universitas Internasional Batam, 2023)
Purpose - The purpose of this study is to investigate the impact of human resources, national internal control systems, and information technology on local government accountability reports. Subsequently, to demonstrate this explanation, the analyst extraordinary inquired about the quality of Neighbourhood Government Consumption Responsibility Reports (Case Consider on UPPDs all through Central Java). Research Method - This survey used primary data collected from 37 respondents. Data were collected using questionnaires that were sent personally to the Head of the Sub-Division of Administration, Administrative Staff, and the Expenditure Treasurer. An analysis of multiple linear regressions was performed using a quantitative approach. Findings - The study shows that local government accounting quality is positively impacted by human resources, internal control systems, and information technology. As this study focuses only on human resources, internal control systems, and information technology. It is suggested that future studies use more or different contextual variables and different measurement instruments. Implication - This study recommends local government to increase the quality accountability report. Human resources capabilities, the application of internal control systems, and the use of information technology units cannot be separated from the quality of the financial management area. This is because the local government is accountable to the central government, DPRD, and the community. Increasing the quality of financial reports will improve public trust in local government.